Projeção da produção utilizando curvas de sítio anamórficas e polimórficas em povoamentos de Eucalyptus grandis W. Hill. Ex. Maiden - Scavinski, Vanessa (2014)
This study aimed to evaluate the influence of anamorphic and polymorphic site curves at the modeling of growth and yield in Eucalyptus grandis stands. The studied area is located in the São Paulo state and involved the regions of Botucatu and Itapetininga. Data from Continuous Forest Inventory (CFI) were utilized, with measurements from 2001 to 2012, covering ages from 12 to 96 months. To generate the site curves, the Schumacher and Chapman-Richards models were adjusted in their anamorphic and polymorphic forms. The site curves were constructed by algebraic difference method. The models were evaluated with the statistics: percentage of estimated standard error (Syx%), coefficient of determination adjusted (R²ajust) and by graphical distribuition of residuals. Anamorfism of polymorphism tests were also conducted and especially the stability of site curves along the years was analyzed, with data from remeasurements of permanent plots. Clutter (1963) model was adjusted to estimate the production using the estimated site index from selected equation, in the anamorphic and polymorphic forms. Then, an analysis of variance was applied to compare the observed yields in the inventory with projection of the production obtained from the site curves anamorphic and polymorphic. The results demonstrated that Chapman-Richards biological model was superior than Schumacher model to both adjustment: anamorphic and polymorphic. The Clutter production model was adequate to project the basal area and volume production, providing consistent values from a statistical and biological perspective. The production prognosis with the Clutter model using site curves anamorphic or polymorphic, generated similar results in the studied region.